Juridical, deontological and ethical issues of the prescription of the hormonal contraceptives. - Casini, Marina; Spagnolo, Antonio G. (Medicina e Morale, 2010)
Faced with woman's request, must the prescription of estroprogestinic substances with contraceptive function be looked as an obligatory act for the physician or has the physician got a freedom's space to set himself against the request and to follow the dictates of conscience? This question, coming out as a consequence of a Milan's Tribunal sentence (1997), is faced beginning from a recognitive's inquire, of legal nature, pertinent the introduction of contraception in our ordinance. Then the Authors propose the triple distinction: the so-called "emergency contraception", contraceptives that could have an abortive effect and the real contraception. While in the first case it is possible to recur to the art. 9 of the Law 194/1978 (conscientious objection to the abortion), in the second and in the third case the letter and the ratio of the art. 9 lead to an its inapplicability. But this doesn't mean to force the physician to make services against his conscience or his clinical belief. By the light of some norms of the sanitary laws and deontological code, the central role of the confidence in the "physician-patient" relationships and the criterions of the freedom choice which presides this relationship are evident. The fiduciary character based on the free choice includes also the sphere of the physician's moral beliefs. So he can rely on a margin of freedom to voice contrariety in which requested by the patient. And the patient can avail himself of his freedom to change physician.